2003
DOI: 10.1002/eqe.303
|View full text |Cite
|
Sign up to set email alerts
|

Input and system identification of the Hualien soil–structure interaction system using earthquake response data

Abstract: SUMMARYThis paper presents an input and system identiÿcation technique for a soil-structure interaction system using earthquake response data. Identiÿcation is carried out on the Hualien large-scale seismic test structure, which was built in Taiwan for international joint research. The identiÿed quantities are the input ground acceleration as well as the shear wave velocities of the near-ÿeld soil regions and Young's moduli of the shell sections of the structure. The earthquake response analysis on the soil-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The present study conÿrms the 15-18% di erence between the shear-wave velocities in directions D 1 and D 2 in the top layer of soil below the foundation. Since similar results have been found [13][14][15][16] from analyses of earthquake ground motions recorded at free-ÿeld downhole arrays located away from the foundation it must be concluded that soil anisotropy must be involved.…”
Section: Revised Structural Modelsupporting
confidence: 69%
“…The present study conÿrms the 15-18% di erence between the shear-wave velocities in directions D 1 and D 2 in the top layer of soil below the foundation. Since similar results have been found [13][14][15][16] from analyses of earthquake ground motions recorded at free-ÿeld downhole arrays located away from the foundation it must be concluded that soil anisotropy must be involved.…”
Section: Revised Structural Modelsupporting
confidence: 69%